MEASURING AND ANALYZING THE RELATIONSHIP BETWEEN THE INFLATION RATE AND THE UR IN IRAQ FOR THE PERIOD (2003-2023) - Razan Sirwan Hameed; Assi.Prof. Dr. Bushra Abdel Bari Ahmed (Scholar Express Journals, 2024)
The research is important as it examines unemployment, as the most important macroeconomic problems in Iraq, while its goal was to evaluate and analyze the inflation rate effect on the general Iraqi unemployment from 2003-2023. The study dealt with the fundamentals of both the inflation rate, the overall unemployment rate, and the relationship between these two variables by examining their economic and econometric situation. The study has been used descriptive approach in the analysis of the data of dependent variable- the total UR (UR), and the independent variable- inflation rate data (INF), and to the Phelps Perron test (PP). The study variable addition degree is a mixture of type I (0) and type I (1), and thus the model was evaluated based on the ARDL selfregression methodology. The boundary test for cointegration shows cointegration relationship for the model making the analysis short term, and the assessed model was successful in every standard quality test (autocorrelation, heterogeneity of variance, normal distribution of residues). In addition, it was stable according to the tests (CUSUM). The most important results of the research are, the inflation rate in Iraq decreased during the study in second half in reference to the success of the fiscal and monetary policies in controlling the inflation rate. The average unemployment in this work was higher than the universally accepted rates of (2%-5%) relative to the poor planning in Iraq and the absence of a plan for absorbing the rising labor forces. The relationship between the inflation and the unemployment rates in Iraq was negative and mean. Yet the size of the impact was very weak, and the research came out with recommendations, the most important of which are, the Central Bank of Iraq must address the negative effects of the decision to raise the exchange rate to avoid the continuous rise in inflation rates. Iraq needs future plans for the reduction of the general unemployment, absorbing the rise in the labor force, and paying attention to develop education and technology. The private sector should be given more opportunities and improve economic activities for providing more jobs and take in more workforce, and to raise investment in all sectors and enlarge the government investment spending for reducing the UR and prevent it.
Keywords: Inflation Rate; Public Spending